2017
DOI: 10.3892/mmr.2017.6988
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism of frailty and cognitive impairment: Potential underlying mechanisms

Abstract: The aim of the present study was to assess systematically gender differences in susceptibility to frailty and cognitive performance decline, and the underlying mechanisms. A systematic assessment was performed of the identified reviews of cohort, mechanistic and epidemiological studies. The selection criteria of the present study included: i) Sexual dimorphism of frailty, ii) sexual dimorphism of subjective memory decline (impairment) and atrophy of hippocampus during early life, iii) sexual dimorphism of late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 177 publications
(213 reference statements)
0
14
0
Order By: Relevance
“…Depression can lead to the upregulation of tumor necrosis factor (TNF) and interleukin (IL)-6. Inflammatory cytokines can penetrate the blood-brain barrier, act on skeletal muscle, accelerate the occurrence of sarcopenia and cognitive dysfunction, and eventually lead to CF [49]. Depression in the aging population is characterized by less verbalization, less movement, mental fatigue, unwillingness to communicate with others, and the continuous lack of physical activity and interpersonal communication, leading to cognitive decline and physical frailty [49].…”
Section: Discussionmentioning
confidence: 99%
“…Depression can lead to the upregulation of tumor necrosis factor (TNF) and interleukin (IL)-6. Inflammatory cytokines can penetrate the blood-brain barrier, act on skeletal muscle, accelerate the occurrence of sarcopenia and cognitive dysfunction, and eventually lead to CF [49]. Depression in the aging population is characterized by less verbalization, less movement, mental fatigue, unwillingness to communicate with others, and the continuous lack of physical activity and interpersonal communication, leading to cognitive decline and physical frailty [49].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that females are more vulnerable than males to substantial loss of muscle (Cruz-Jentoft et al, 2010) and that the prevalence of frailty is higher among females (Ruan et al, 2017). Recent research has shown that females are more vulnerable than males to substantial loss of muscle (Cruz-Jentoft et al, 2010) and that the prevalence of frailty is higher among females (Ruan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The second biological mechanism that is relevant to explain gender differences in dexterity decline is age-related reduction in muscle mass and strength. Recent research has shown that females are more vulnerable than males to substantial loss of muscle (Cruz-Jentoft et al, 2010) and that the prevalence of frailty is higher among females (Ruan et al, 2017). Therefore, females may experience an earlier decline in hand strength and function than males.…”
Section: Introductionmentioning
confidence: 99%
“…DHEA is a precursor to androgens and estrogen and its conversion into estrone is the major source of estrogen in postmenopausal women (Rodwell et al, 2018). DHEA-S is the most abundant steroid hormone in serum (Ruan et al, 2017) and can modulate lipid and glucose metabolism (Yen and Laughlin, 1998). As DHEA-S levels decrease, pain threshold and tolerance decrease (De Abreu Freitas., 2012).…”
Section: Discussionmentioning
confidence: 99%